Stock market reaction to COVID-19: Evidence in customer goods sector with the implication for open innovation - Zaky Machmuddah; St. Dwiarso Utomo; Entot Suhartono; Shujahat Ali; Wajahat Ali Ghulam (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The coronavirus pandemic has spread all over the world, affecting both the health and economic sectors. The aim of this research was to observe stock prices of customer goods before and after the COVID-19 pandemic using event study and the comparison test. The sample included data of daily closing stock prices and volume of stock trade during the three months before (-90 days) and after (+90 days) the occurrence of the COVID-19 pandemic ongoing, totaling 2670 observation data both before and after the COVID-19 pandemic, for a total of 5340. The research findings indicate a significant difference between the daily closing stock price and volume of stock trade before and after the COVID-19 pandemic. The current research has both theoretical and practical implications: the findings strengthen the efficient market hypothesis, which states that the more complete the provided information, the more efficient the market. The practical implication is that investors should be careful when choosing to invest. Investors should choose customer goods sector companies that provide products that are much needed by customers, for example, pharmacy, food, beverages, etc. Future research is needed to investigate the long-term impact of the pandemic on the economy.
Keywords: G15; G35; M21; 650; stock price; stock trading volume; market reaction; coronavirus; COVID-19